Ulcerative colitis case beginning during pregnancy in a patient with antiphospholipid antibody syndrome - Yüksel ATEŞ; Murat ASLAN; Ahmet TÜZÜN; Sait BAĞCI; Kemal DAĞALP (Turkish Journal of Gastroenterology, 2019)
-